불안정성 대퇴부 전자간 골절의 무시멘트 인공관절 전치환술에서 이중 강선, 이중 고리, 8자 고정술을 이용한 대전자부 골절 고정술 - 남호진; Ho Jin Nam; 선두훈; Doo Hoon Sun; 장성원; Seong Won Jang (Hip & pelvis, 2012)
목적: 고령의 환자들에서 불안정한 대퇴골 전자간 골절의 치료로써 무시멘트 고관절 인공관절 전치 환술은 대퇴골 전자간 골절 치료로써 금속판이나 금속정 등의 내고정술 이외의 또 하나의 수술법으로 생각되고 있으며 대전자부 골편의 유합이 중요한 관심사 중의 하나이다. 이에 저자들은 이중 강선, 이중 고리, 8자 고정술을 이용한 대전자부 골편의 고정에 있어서 고정 방법에 따른 임상 및 방사선학적 결과를 발표하고자 한다. 대상 및 방법: 2010년 4월부터 2012년 2월까지 고관절의 불안정한 전자간 골절로 무시멘트 인공관절 전치환술 및 직경 1.0 mm의 이중 강선, 이중 고리, 8자 고정술을 시행 받은 20명 20예를 대상으로 하였다. 평균 연령은 71.1세(57-86세)였고 남자가 9명, 여자가 11명이었으며, 평균 추적관찰 기간은 6개월이었다. 술 후 환자들의 상태를 Harris hip score를 이용하여 평가하였다. 결과: 본 연구에서 수술 시간은 평균 95분, 수술 시 실혈량은 평균 800 cc였다. 최종 추시에서 Harris hip score는 평균 92.7점이었으며, 15예에서 보행거리의 감소없이 일상생활이 가능하였다. 술 후 고관절 탈구가 발생한 것은 1예였고, 고정 강선의 파손은 1예였다. 욕창과 심부정맥 혈전증 및 폐색전증이 발생한 사례는 없었다. 또한, 방사선학적으로 모든 사례에서 대퇴 주대는 해리 없이 잘 유지되었고, 13예에서 골절주위의 골생성을 확인할 수 있었으며, 골용해 소견을 보인 예는 없었다. 결론: 불안정성 대전자 골절 치료시 무시멘트형 인공고관절 치환술을 시행할 때 대전자부 골편을 고정하는데 이중강선, 이중고리, 8자 고정술을 이용한 강선 결박술이 유용한 방법으로 사료된다. 그러나 정복 방법의 개발과 함께 장기간의 추시결과에 대한 연구가 더욱 필요 할 것으로 사료된다. Purpose: Non-cement total hip arthroplasty for unstable intertrochanteric fracture in elderly patients is regarded as another surgical technique preventing complications such as non-union, long term limitation of weight bearing, pressure sore, pulmonary thromboembolism after open reduction or closed reduction with intramedullary nailing, or plate fixation. We would like to announce the short-term results of primary noncement total hip arthroplasty with double strands and double loops figure of 8 wiring for unstable intertrochanteric fracture in elderly patients. Materials and Methods: All of the 20 patients admitted to the hospital between April 2010 and February 2012 who underwent non-cement total hip arthroplasty with double strands and double loops figure of 8 wiring for unstable intertrochanteric fractures were evaluated. The mean age was 71.1(57-86), there were nine males, and 11 females, with an average follow up period of six months. The post-operative state was evaluated by Harris hip score. Results: The mean operation time was 95 min, and the average blood loss was 800 cc. Mean Harris hip score at the last available follow-up was 92.7, and, among the patients, 15 had all functions of daily life without limitation of walking distance, one had hip dislocation, one had breakage of strands. Pressure sore, deep vein thrombosis, and pulmonary thromboembolism were absent. Radiography at the last available follow-up showed no loosening of the femoral stem in any of the patients, and 13 patients had osteogenesis around the fracture site, and there was no osteolysis. Conclusion: Primary non-cement total hip arthroplasty with double strands and double loops figure of 8 wiring in elderly patients with unstable intertrochanteric fractures showed satisfactory results. These results are expected to be useful for further studies with a long-term follow-up and in development of a reduction method.